Exploration of suitable in vitro simulated digestion model for lipid oxidation of flaxseed oil emulsion during digestion. (15th April 2022) - Li, Xiaowen; Huang, Qingde; Wang, Xintian; Zhang, Mingkai; Quan, Shuang; Geng, Fang; Chen, Hongjian; Deng, Qianchun
Abstract: BACKGROUND: The INFOGEST model is a standardized general in vitro digestion study, but it cannot accurately simulate the fatty acid release process of lipids in the stomach and small intestine. In this study, the internationally universal INFOGEST 2019 was used as the basic model and flaxseed oil emulsion was used as the research object. In various improvement models, the effect of fatty acid release rate on the oxidation stability of flaxseed oil was assessed by adding rabbit stomach extract and changing the order of bile salts addition. RESULTS: With the presence of rabbit gastric extract, flaxseed oil emulsion flocculation and coalescence in stomach were reduced, and the absolute value of ζ ‐potential increased. Moreover, the release rate of fatty acids in the small intestine increased by 12.14%. The amount of lipid oxidation product (i.e. hexanal) in the gastric and intestinal phases increased by 0.08 ppb. In addition, the fatty acid release rate in the small intestine phase increased by 5.85% and the hexanal content increased by 0.011 ppb in the digestion model of adding bile salts before adjusting the pH in the small intestine phase compared with the model of adjusting the pH first and then adding bile salts. CONCLUSION: The results obtained from this study will contribute to finding the most suitable static digestion model for simulating digestion and oxidation of lipid during lipid gastrointestinal digestion. © 2022 Society of Chemical Industry.